Developing Marketing Strategy Using Promotion Mix Method to Increase Purchase Intention at PT Sinar Dempo Bus Service - Abdallah, Muhamad Fadel (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
In the fast-paced digital era, the bus transportation industry is undergoing significant transformation, especially in how consumers behavior when booking transportation. PO Sinar Dempo, a well-established bus operator in Sumatra, recognizes the need to adapt by developing an integrated marketing communication (IMC) strategy. This study aims to explore how promotional elements such as advertising, sales promotion, personal selling, and digital marketing influence consumer attitudes and, ultimately, their online ticket purchase intentions. A quantitative approach was applied by distributing a structured questionnaire to 250 respondents who are users of Sinar Dempo services. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the SmartPLS 4.0 software. The findings reveal that digital marketing, advertising, personal selling and sales promotion have a significant impact on shaping consumer attitudes, which then influence their intention to purchase.  Beyond promotional impacts, this research also examines both internal and external strategic factors that influence Sinar Dempo competitive position. Internal analysis using STP (Segmentation, Targeting, Positioning), the 7P Marketing Mix, and VRIO framework was complemented by external analysis through Porter’s Five Forces, PESTEL, competitor mapping, and customer analysis. These insights were synthesized into a comprehensive TOWS Matrix to formulate actionable strategies. Through this holistic approach, Sinar Dempo is expected to strengthen customer loyalty, expand its digital market presence, and optimize service offerings that cater to both modern digital consumers and those who still prefer traditional booking methods.